Cursed : an anthology of dark fairy tales - Gaiman, Neil; Yolen, Jane; Fowler, Karen Joy; Carey, M. R., 1959-; Henry, Christina, 1974-; Golden, Christopher; Lebbon, Tim; Smith, Michael Marshall; Anders, Charlie Jane; Williams, Jen, (Fiction writer); Ward, Catriona; Brogden, James; et al. (Titan Books, 2020)
"All the better to read you with... It's a prick of blood, the bite of an apple, the evil eye, a wedding ring or a pair of red shoes. Curses come in all shapes and sizes, and they can happen to anyone, not just those of us with unpopular stepparents... Here you'll find unique twists on curses, from fairy tale classics to brand-new hexes of the modern world -- expect new monsters and mythologies as well as twists on well-loved fables. Stories to shock and stories of warning, stories of monsters and stories of magic." --